The Unheard Voices behind the Telephone - Kerur, Vandana (THE PRIMARY TEACHER, 2017)
The ringing of a cell phone or landline draws immediate attention as it connects one with people across vast distances. Many would remember the name of the inventor of the telephone, i.e., Alexander Graham Bell. But what many may not know is that this great inventor worked tirelessly for the deaf. The influence behind this lifelong dogged effort came from his immediate family members — the emotional motivation grew out of love for his mother and his wife (both of whom were deaf), the cognitive connect was developed and encouraged by the men in the family — for Bell’s father and grandfather were experts on the mechanics of voice and elocution. His brother (who died at an early age due to tuberculosis) was also interested in the production of sounds.